Endogenous Business Cycles and Systematic Stabilization Policy - Marta Aloi; Teresa Lloyd-Braga; Hans Jørgen Whitta-Jacobsen (University of Copenhagen, Economic Policy Research Unit (EPRU), 2002)
We study the effects of fiscal policy rules on the determinacy of rational expectations equilibrium in a perfectly competitive monetary model with constant returns. Government spending implies a distortion of the monetary steady state due to the implied taxation. We show that policy rules that let the GNP share of government spending sufficiently negatively on increases in GNP stabilize the economy with respect to endogenous fluctuations for arbitrarily little distortion of the steady state of which stabilization occurs. The rules do not involve lump sum taxation, negative income taxation, or exact knowledge of the economy's laissez faire steady state. (JEL E32 and E63 - Keywords: Endogenous business cycles, stabilization policy - Running title: Endogenous Fluctuations and Stabilization Policy)
Keywords: 330; Monetäre Wachstumstheorie; Konjunkturtheorie; Finanzpolitik; Regelbindung; Globalsteuerung; Rationale Erwartung; Theorie